Novel Pyoverdine Inhibitors Mitigate Pseudomonas aeruginosa Pathogenesis - Kirienko, Daniel R.; Kang, Donghoon; Kirienko, Natalia V. (Frontiers in Microbiology, 2019)
Pseudomonas aeruginosa is a clinically important pathogen that causes a variety of infections, including urinary, respiratory, and other soft-tissue infections, particularly in hospitalized patients with immune defects, cystic fibrosis, or significant burns. Antimicrobial resistance is a substantial problem in P. aeruginosa treatment due to the inherent insensitivity of the pathogen to a wide variety of antimicrobial drugs and its rapid acquisition of additional resistance mechanisms. One strategy to circumvent this problem is the use of anti-virulent compounds to disrupt pathogenesis without directly compromising bacterial growth. One of the principle regulatory mechanisms for P. aeruginosa’s virulence is the iron-scavenging siderophore pyoverdine, as it governs in-host acquisition of iron, promotes expression of multiple toxins, and is directly toxic. Some combination of these activities renders pyoverdine indispensable for pathogenesis in mammalian models. Here we report identification of a panel of novel small molecules that disrupt pyoverdine function. These molecules directly act on pyoverdine, rather than by affecting its biosynthesis. The compounds reduce the pathogenic effect of pyoverdine and improve the survival of C. elegans when challenged with P. aeruginosa by disrupting only this single virulence factor. Finally, these compounds can synergize with conventional antimicrobials, forming a more effective treatment when combined. These data suggest that these compounds may help to identify, or be expanded to produce, viable drug leads in their own right. Finally, they also serve as useful tool compounds to probe pyoverdine activity.